Operasi dan Pemeliharaan Pemutus Tenaga (PMT) menggunakan Media Gas SF6 di Gardu Induk 150 Kv Purbalingga - Carolus Borromeus Krishna Sampurno; Siska Irma Budianti; Nota Ali Sukarno; Abdul Azis; Aldean Obiyasi (Fuse-teknik Elektro, 2026)
SF6 gas-insulated circuit breakers play an important role in power transmission systems by interrupting and connecting electrical current during both normal and fault conditions. This study aims to analyze the operation and maintenance of SF6 circuit breakers at the 150 kV Purbalingga Substation and evaluate their compliance with the operational standards of PT PLN (Persero). The research methods included field observation, interviews with substation operators, documentation study, and literature review. The results indicate that the SF6 gas pressure remained within the normal operating range of 0.55–0.65 MPa, the mechanical operating system functioned properly, and no significant gas leakage was detected. Maintenance activities were carried out periodically through daily, weekly, monthly, and annual inspections in accordance with PLN’s standard operating procedures. In addition, circuit breaker operations, both remotely through SCADA and manually by operators, were performed according to established switching procedures. The implementation of disciplined preventive maintenance enabled the SF6 circuit breakers at the 150 kV Purbalingga Substation to support the reliability and continuity of electrical power transmission effectively.